The concept of social capital and its usage in educational studies - Guðmundsson, Gestur; Mikiewicz, Piotr (Wydawnictwo Naukowe UAM, 2012)
The aim of the article is to elaborate the theoretical background of the social capital concept. During the last decade the concept of Social Capital has probably been the most widely used concept in international sociology and on the intersection of sociology and educational studies. Social capital has become one of the basic explanatory variables for social inequalities, underdevelopment of some countries and neighbourhoods, level of delinquency and quality of life (in economic and psychological meaning). Often in sociological readings one can find misunderstanding of the meaning of the social capital concept and misleading presumptions of the social mechanisms it is meant to explain. In this study authors examine the meaning of the term in main theoretical contexts and its usage in in educational research.
Koncepcja kapitału społecznego i jej zastosowanie w badaniach edukacyjnych
Keywords: social capital; education; Pierre Bourdieu; James Coleman; Robert D. Putnam